Polyurethanes for Medical Use - Tanja Pivec; Majda Sfiligoj Smole; Petra Gašparič; Karin Stana Kleinschek (Tekstilec, 2017)
Polyurethanes are synthetic copolymers containing urethane linkages in their complex chemical structure. They consist of three monomers: a diisocyanate, a polyol and a chain extender, which enables the synthesis of an endless number of polyurethanes with diff erent physicochemical and mechanical properties. The physicochemical properties of various polyurethanes are largely dependent on the conformation of polyols, which may contain two or more different polyols, stabilisers, catalysts, liquids or solid additives and, in the case of foams, foaming agents. Depending on the structure of the polyols, i.e. the length of the chain, structure of the units (aliphatic or aromatic), ester or ether groups, or functionalisation by hydroxyl groups, polyurethanes may be fl exible or rigid, and therefore suitable for various applications. In addition to the physical and chemical structure of polyurethanes, this review paper specifi cally addresses their use in medicine, particularly in wound dressings, tissue engineering scaff olds and drug delivery with nanoparticles and nanocapsules, and provides guidelines for the development of new biodegradable polyurethane materials